Preparation method and application of NiSe2-coated CuSe positive electrode material for rechargeable magnesium battery

Synthesis of NiSe2@CuSe heterostructured cathode material by hydrothermal method solves the problems of slow ion diffusion kinetics and poor stability of existing magnesium battery cathode materials, achieves high specific capacity and excellent cycling performance, and significantly improves the performance and application potential of magnesium batteries.

CN119764427APending Publication Date: 2025-04-04HENAN UNIVERSITY
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510040243.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing rechargeable magnesium battery positive electrode materials have problems such as slow ion diffusion kinetics, low specific capacity, insufficient cycle life and poor stability.

Method used

The NiSe2@CuSe heterostructure positive electrode material was synthesized by hydrothermal method. This material was prepared by reacting selenium powder, nickel hexahydrate and copper chloride in ultrapure water, and high-temperature reaction in polytetrafluoroethylene liner.

Benefits of technology

It achieves high specific capacity and excellent cycling performance, can achieve a specific capacity of 179.9 mAh/g at a current density of 200 mA/g, and maintains a stable cycle of more than 400 cycles, significantly improving the stability and application potential of magnesium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a NiSe2-coated CuSe positive electrode material for a rechargeable magnesium battery. According to the method, NiSe2-coated CuSe with a heterostructure is synthesized by adopting a simple hydrothermal reaction, and the NiSe2-coated CuSe is applied to a magnesium battery. According to the invention, a simple and convenient preparation process is adopted, and the magnesium battery positive electrode material with excellent performance is successfully developed. The material not only has excellent magnesium storage performance, but also shows good cycling stability in the charging and discharging process, which indicates that the material has huge application potential in the development of the magnesium battery technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of magnesium ion battery materials, and specifically relates to a NiSe for rechargeable magnesium battery obtained by a hydrothermal method. 2 @Preparation method of CuSe heterostructure positive electrode material and its application in magnesium battery field. Background Art

[0002] With the growing demand for battery capacity in electric vehicles and grid energy storage, the energy density of traditional rechargeable lithium batteries has gradually been unable to meet future energy needs. At the same time, the high cost of lithium resources and the safety risks caused by the dendrite problem of lithium batteries are also driving the development of new ion battery technologies. Metal batteries such as sodium, magnesium, and calcium are regarded as potential substitutes for lithium-ion batteries (LIBs) due to their abundant reserves and their respective advantages. In particular, magnesium-ion batteries (MIBs) have a higher energy density (the energy density of magnesium metal at 3383 mAh / cm³ is almost twice that of lithium metal at 2046 mAh / cm³), a lower reduction potential (–2.4 V vs. SHE) and abundant magnesium resource reserves show potential as a substitute for lithium-ion batteries. In addition, magnesium batteries have attracted much attention for their non-toxicity, high safety and low anode dendrites, which make them more suitable for electric vehicle applications and have broad application prospects in military and civilian fields. However, traditional magnesium-ion batteries also have some disadvantages, including the formation of a passivation film at the magnesium anode-electrolyte interface, a narrow electrochemical window and slow magnesium ion diffusion kinetics. These factors not only reduce the conductivity of electrons and ions, but also hinder the reversibility of magnesium deposition and dissolution processes, thereby limiting the development of magnesium-ion batteries on the road to commercialization.

[0003] At present, the research focus of magnesium battery positive electrode materials is to develop new materials that can achieve reversible insertion and extraction of magnesium ions, and ensure that these materials have good compatibility with the electrolyte. Common positive electrode materials include inorganic embedded positive electrode materials, conversion positive electrode materials, organic positive electrode materials, etc. Selenium has the characteristics of large anion radius, high conductivity, low electronegativity, and there is a special electron orbital hybridization between selenium 3d and transition metal M 4p. Therefore, selenide is regarded as a potential choice for high energy density rechargeable magnesium battery positive electrode materials. Compared with metal sulfides, selenides exhibit superior conductivity, and the unique electron orbital mixing between selenium and transition metals has opened up new ways for the application of transition metal selenides in electrochemical energy storage technologies such as magnesium-based batteries. Therefore, conversion selenides are regarded as a highly potential high energy density magnesium battery positive electrode material.

[0004] Based on this, this application was developed. Summary of the invention

[0005] The present invention aims to overcome the defects of the prior art and provide a heterostructure NiSe for rechargeable magnesium batteries. 2 @CuSe positive electrode material. This positive electrode material solves the problems of low specific capacity, insufficient cycle life and poor stability caused by slow ion diffusion kinetics and selenide shuttle effect in current rechargeable magnesium battery positive electrode materials.

[0006] The present invention also provides the above-mentioned positive electrode material NiSe for rechargeable magnesium battery 2 @Preparation method and application of CuSe positive electrode material.

[0007] To achieve the above object, the present invention adopts the following technical solution: NiSe for rechargeable magnesium battery 2 The preparation method of @CuSe positive electrode material comprises the following steps: Step 1: Add selenium powder, nickel chloride hexahydrate and anhydrous cupric chloride into ultrapure water, and mix them by stirring for 1 to 5 hours to obtain solution A; Step 2: Slowly add ammonia water and a reducing agent to solution A to obtain solution B; Step 3: Transfer solution B to a polytetrafluoroethylene liner, react at 100-200 °C for 10-20 h, cool to room temperature, wash and dry to obtain.

[0008] Specifically, in step 1, the molar ratio of the selenium powder, nickel chloride hexahydrate and anhydrous cupric chloride can be (3-6):(0.5-3):(0.5-3).

[0009] Specifically, in step 2, the ammonia water NH 3 The molar ratio of selenium powder to nitric acid can be 16-18: 1. Ammonia water with a mass percentage concentration of 15% to 30% can be used for addition.

[0010] Furthermore, in step 2, the reducing agent may be sodium borohydride or hydrated hydrazine, and the molar ratio of the reducing agent to the selenium powder may be 12-16:1.

[0011] Specifically, in step 3, the temperature can be raised to 100-200°C at a heating rate of 5-15°C / min, preferably at a heating rate of 10°C / min. After washing with anhydrous ethanol and deionized water alternately, the mixture is dried at 40-80°C for 10-30 h. The reaction is preferably carried out at a temperature of 140-150°C for 15 h.

[0012] The present invention provides a NiSe for rechargeable magnesium battery prepared by the above preparation method. 2 @CuSe positive electrode material.

[0013] The present invention also provides the above-mentioned rechargeable magnesium battery using NiSe 2 @Application of CuSe positive electrode material in the preparation of magnesium battery positive electrode or magnesium battery.

[0014] The present invention also provides a rechargeable magnesium battery positive electrode, wherein the rechargeable magnesium battery positive electrode comprises the rechargeable magnesium battery NiSe 2 @CuSe positive electrode material.

[0015] The present invention also provides a rechargeable magnesium battery positive electrode, which is prepared by the following steps: Step 1: Place the NiSe 2 @CuSe positive electrode material, conductive carbon black, polyvinylidene fluoride, mixed and ground in a mass ratio of 8~5:1~4:1; Step 2: Add an appropriate amount of N-methylpyrrolidone and stir for 10-36 h to mix well to obtain a slurry with a concentration of 0.1-0.2 g / mL; Step 3: Evenly coat the slurry from step 2 on the carbon cloth (the coating amount of active material is 2-5 mg / cm 2 ), vacuum dry at 80~150 ℃ for 3~10 h, cut as required to obtain the positive electrode.

[0016] The present invention also provides a rechargeable magnesium battery, which is prepared in a glove box filled with argon (the content of water and oxygen is both less than 0.01 ppm), with the rechargeable magnesium battery positive electrode as the positive electrode, the polished magnesium foil as the negative electrode, the glass fiber filter paper (Whatman GF / D) as the diaphragm, and the ethylene glycol dimethyl ether solution containing magnesium bistrifluoromethanesulfonyl imide, anhydrous aluminum chloride, and anhydrous magnesium chloride as the electrolyte, to assemble into a button battery.

[0017] The specific electrolyte ratio is: magnesium bis(trifluoromethanesulfonyl)imide, anhydrous aluminum chloride, and anhydrous magnesium chloride are added to ethylene glycol dimethyl ether in a mass ratio of 1:1:2 to prepare an electrolyte with a concentration of 0.4-0.5 g / mL.

[0018] Compared with the prior art, the present invention has at least the following advantages and beneficial effects: 1) The present invention uses a simple hydrothermal reaction to synthesize NiSe with heterogeneous structure 2 @CuSe, the obtained product has high crystallinity, small grains and uniform distribution. 2 @CuSe positive electrode material was used as the positive electrode material for magnesium ion battery for electrochemical testing. The electrochemical performance test results show that the rechargeable magnesium battery of the present invention uses NiSe 2@CuSe positive electrode material has a high specific capacity, excellent cycle performance and good rate performance. It has a high specific capacity of 179.9 mAh / g at a current density of 200 mA / g and can maintain a stable cycle for more than 400 cycles. It has a higher charge and discharge specific capacity and longer cycle performance than the same type of selenide positive electrode materials.

[0019] 2) NiSe for rechargeable magnesium battery provided by the present invention 2 The preparation method of @CuSe positive electrode material has a simple preparation process, high yield and strong repeatability, which provides a new method for the use of selenide in rechargeable magnesium battery positive electrode materials and has important application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The positive electrode material of the rechargeable magnesium battery of the present invention (NiSe 2 @CuSe) SEM and EDS images; a, b are SEM images at the scale of 200 nm and 100 nm, respectively, c is the EDS general map of Ni Cu Se C, d is the Ni element distribution map, e is the Cu element distribution map, and f is the Se element distribution map; Figure 2 The positive electrode material of the rechargeable magnesium battery of the present invention (NiSe 2 @CuSe) XRD pattern; Figure 3 The positive electrode material (NiSe 2 @CuSe) assembled into a button cell and then electrochemically tested at a current density of 200 mA / g for cycling specific capacity; Figure 4 The positive electrode material (NiSe 2 @CuSe) assembled into a button cell. DETAILED DESCRIPTION

[0021] The technical solution of the present invention is further described in detail below in conjunction with the embodiments, but the protection scope of the present invention is not limited thereto.

[0022] In the following examples, unless otherwise specified, the raw materials used are common commercial products that can be directly purchased or can be prepared using conventional techniques in the art.

[0023] Room temperature refers to 25±5°C.

[0024] Embodiment 1: A NiSe rechargeable magnesium battery 2 The preparation method of @CuSe positive electrode material is as follows: 1) Add 5 mmol of selenium powder, nickel chloride hexahydrate and anhydrous copper chloride in a molar ratio of 4:2:1 into 60 mL of ultrapure water and stir for 5 h to mix well to obtain solution A; 2) Slowly add 8 mL of 20% ammonia water and 4 mL of 80% hydrated hydrazine solution to solution A to obtain solution B; 3) Transfer solution B to a polytetrafluoroethylene liner, heat it to 150 °C at a rate of 10 °C / min, react at 150 °C for 15 h, and then cool it to room temperature. Wash it with deionized water and ethanol alternately for 3 times, and then vacuum dry it at 60 °C for 24 h to obtain NiSe 2 @CuSe positive electrode material.

[0025] Embodiment 2: The preparation method of the positive electrode sheet of a rechargeable magnesium battery is as follows: The NiSe prepared in Example 1 2 @CuSe positive electrode material, conductive carbon black and polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 7:2:1 and added to an appropriate amount of N-methylpyrrolidone (NMP), and then stirred until the slurry showed a flowable uniform slurry state (slurry concentration 0.15 g / mL). After stirring, the above slurry was evenly coated on the carbon cloth ((the coating amount of active material was 3 mg / cm 2 )), first dried in a forced air drying oven at 60 °C for 30 min, then transferred to a vacuum drying oven and dried at 120 °C for 5 h. The dried positive electrode material was cut into pieces using a circular mold with a diameter of 12 mm to obtain a positive electrode sheet.

[0026] Embodiment 3: The preparation method of button-type magnesium battery is as follows: The assembly process of button cell CR2032 is carried out in a glove box filled with argon, where the water oxygen value is less than 0.01 ppm. The positive electrode of the rechargeable magnesium battery prepared in Example 2 is used as the positive electrode, the polished magnesium foil is used as the negative electrode, the glass fiber filter paper (Whatman GF / D) is used as the diaphragm, and the ethylene glycol dimethyl ether solution containing bistrifluoromethanesulfonyl imide magnesium, anhydrous aluminum chloride, and anhydrous magnesium chloride is used as the electrolyte (the specific electrolyte ratio is: bistrifluoromethanesulfonyl imide magnesium, anhydrous aluminum chloride, and anhydrous magnesium chloride are added to ethylene glycol dimethyl ether in a mass ratio of 1:1:2 to prepare an electrolyte with a concentration of 0.45 g / mL). When assembling the battery, assemble in the order of negative electrode shell, negative electrode magnesium foil, electrolyte, diaphragm, electrolyte, positive electrode sheet, gasket, shrapnel and positive electrode shell. The diameter of the metal negative electrode magnesium foil is 14 mm, the diameter of the diaphragm is 16 mm, the diameter of the positive electrode is 12 mm, and the amount of electrolyte used is 100 μL.

[0027] Example 4 Refer to Example 1, except that, in step 1), the molar ratio of the selenium powder, nickel chloride hexahydrate and anhydrous cupric chloride is 5:3:2.

[0028] Example 5 Refer to Example 1, except that in step 2), the reducing agent is replaced with sodium borohydride.

[0029] Morphology test The present application conducted a morphology test on the positive electrode material prepared in Example 1. Figure 1 The SEM and EDS images of the positive electrode material are shown in Figure 1. a and b are taken at the scale of 200 nm and 100 nm, respectively. It can be found that small nanoparticles grow on the hexagonal nanosheets, indicating that NiSe 2 and CuSe combine well, and the synthesized NiSe 2 @CuSe particle size is between 100~200nm, and ef is an element analysis diagram when shooting at 100nm. It can be seen that the three elements Ni, Cu and Se are evenly distributed.

[0030] Figure 2 XRD test is performed on the synthesized samples to analyze the microstructure of the positive electrode material. 2 The XRD tests of NiSe and CuSe samples were also performed separately as controls. 2 The diffraction peaks of the sample are at 30.250°, 33.895°, 37.154°, 43.159°, 45.531°, 51.149°, 55.943°, 58.140° and 62.560°, which are similar to those of NiSe. 2 The characteristic diffraction peaks at the (200) (210) (211) (220) (221) (311) (230) (321) (400) crystal planes are consistent with those on the standard card (JCPDS No. 41-1495). The diffraction peaks of the CuSe sample can be accurately indexed to the hexagonal CuSe phase (JCPDS No. 34-0171), with six main peaks at 26.904°, 28.427°, 31.488°, 46.317°, 50.362° and 56.929°, corresponding to the (101), (102), (006), (110), (114) and (116) crystal planes of CuSe, respectively. And there are no impurity peaks in each sample. In the synthesized NiSe 2 @NiSe can be observed in CuSe 2 and CuSe, which indicates that NiSe 2 @CuSe was successfully prepared. A small amount of peaks belonging to CuSe did not appear because NiSe2 It is attached to CuSe, which can also be found in the scanning electron microscope. The smaller NiSe 2 Attached to CuSe.

[0031] Electrochemical testing The button-type magnesium battery prepared in Example 3 was tested in a blue electricity test system, and the experimental parameters were set to 0.1-2.1 V and the current density was 200 mA / g.

[0032] Figure 3 The positive electrode material (NiSe 2 @CuSe) assembled into a button cell and then electrochemically tested at a current density of 200mA / g to obtain the cycle specific capacity diagram. Figure 3 As shown, NiSe 2 @CuSe as the positive electrode active material, the maximum discharge capacity of the button-type magnesium battery can reach 179.9 mAh / g at a current density of 200 mA / g, and the discharge capacity can still reach 137 mAh / g after 400 cycles, which is 76.1% of the maximum discharge capacity. 2 Se@CuSe has an excellent magnesium storage property and good cycle stability.

[0033] Figure 4 The positive electrode material (NiSe 2 @CuSe) assembled into a button cell. Figure 4 It can be seen that the discharge capacity can still reach 76.1 mAh / g at a high current density of 500 mA / g, and can still maintain an excellent cycle stability (Coulomb efficiency close to 100%) at a higher current of 1000 mA / g, and after a series of gradient tests, the discharge capacity at a current density of 50 mA / g can still reach a high capacity of 202.6 mAh / g. This result shows that the NiSe prepared in Example 1 2 @CuSe has good rate performance.

[0034] In summary, the positive electrode material NiSe for rechargeable magnesium battery developed by the present invention 2 @CuSe, not only has a simple preparation process, but also exhibits excellent magnesium storage capacity. During the charge and discharge cycle under high current density conditions, the material can still maintain a high specific capacity and exhibit good cycle stability during the charge and discharge process, indicating that it has great application potential in the development of magnesium battery technology.

[0035] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.

Claims

1. A method for preparing a NiSe2@CuSe positive electrode material for a rechargeable magnesium battery, characterized in that: The steps include: Step 1: Add selenium powder, nickel chloride hexahydrate and anhydrous cupric chloride into ultrapure water and mix well to obtain solution A; Step 2: adding ammonia water and a reducing agent to solution A to obtain solution B; Step 3: React solution B at 100-200 °C for 10-20 h, cool to room temperature, wash and dry to obtain.

2. The method for preparing the NiSe2@CuSe positive electrode material for a rechargeable magnesium battery according to claim 1, characterized in that: In step 1, the molar ratio of the selenium powder, nickel chloride hexahydrate and anhydrous cupric chloride is (3-6):(0.5-3):(0.5-3).

3. The method for preparing the NiSe2@CuSe positive electrode material for a rechargeable magnesium battery according to claim 1, characterized in that: In step 2, the molar ratio of NH3 to selenium powder in the ammonia water is 16-18:

1.

4. The method for preparing the NiSe2@CuSe positive electrode material for a rechargeable magnesium battery according to claim 1, characterized in that: In step 2, the reducing agent is sodium borohydride or hydrazine hydrate, and the molar ratio of the reducing agent to selenium powder is 12-16:

1.

5. The method for preparing the NiSe2@CuSe positive electrode material for a rechargeable magnesium battery according to claim 1, characterized in that: In step 3, the temperature is increased to 100-200 °C at a heating rate of 5-15 °C / min; after washing with anhydrous ethanol and deionized water alternately, it is dried at 40-80 °C for 10-30 h.

6. NiSe2@CuSe positive electrode material for rechargeable magnesium battery prepared by the preparation method according to any one of claims 1 to 5.

7. Use of the NiSe2@CuSe positive electrode material for rechargeable magnesium battery according to claim 6 in preparing a positive electrode of a magnesium battery or a magnesium battery.

8. A rechargeable magnesium battery positive electrode, characterized in that: The rechargeable magnesium battery positive electrode comprises the NiSe2@CuSe positive electrode material for a rechargeable magnesium battery according to claim 6.

9. The positive electrode of a rechargeable magnesium battery according to claim 8, characterized in that: Prepared by the following steps: Step 1: Mix and grind the NiSe2@CuSe positive electrode material, conductive carbon black, and polyvinylidene fluoride in a mass ratio of 8-5:1-4:1; Step 2: Add an appropriate amount of N-methylpyrrolidone and mix well to obtain a slurry; Step 3: Evenly coat the slurry in step 2 on the carbon cloth, vacuum dry it, and cut it as required to obtain the positive electrode.

10. A rechargeable magnesium battery, characterized in that: The rechargeable magnesium battery positive electrode according to claim 8 is used as the positive electrode, the polished magnesium foil is used as the negative electrode, the glass fiber filter paper is used as the diaphragm, and the ethylene glycol dimethyl ether solution containing magnesium bistrifluoromethanesulfonyl imide, anhydrous aluminum chloride, and anhydrous magnesium chloride is used as the electrolyte to assemble into a button battery.

Citation Information

Cited By

  • Preparation method and application of magnesium ion battery positive electrode material with heterostructure

    CN120864451A

  • Coated magnesium ion battery positive electrode material and preparation method thereof

    CN122025606A